CONTEXT AND ITS IMPORTANCE IN TRANSLATION - Shahodat Usmanova; Esirgapova Umida (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article describes in detail about context and its importance in translation, translation of lexical units, lexical transformations, comparative study of words in translation, lexical problems of translation, cultural meaning of words in translation.